DNA Barcoding of Rattan (Arecaceae) From Gunung Walat Education Forest, Sukabumi-West Java - Arida Susilowati; Baiquni Rangkuti, Ahmad; Siregar, Ulfa Juniarti; Irmayanti, Laswi; Siregar, Iskandar Zulkarnain (Talenta Publisher, 2021)
Rattan is a forest plant that has high economic and ecological value. This species grows in various habitats because of its good adaptability. Gunung Walat education forest (GWEF) is an ex-situ conservation location owned by IPB University and rattan conservation potential. In 2005 rattan were planted in this area from some material source in Indonesia, but the information regarding its identity was still limited. Therefore, this study aims to identify rattan in GWEF using barcode methods. Four barcoding those were rbcL, matk K, psbA-trnH, and ITS 1 was used for this purpose. Molecular analysis was conducted through DNA extraction using the CTAB method, DNA quality and quantity observation using electrophoresis and Polymerase Chain Reaction (PCR) amplification. The result of this research showed that DNA barcodes show a different